Ocenjevanje tveganja za okolje za humana zdravila - Stanojević, Mark (Farmacevtski vestnik, 2019)
In November 2018, the European medicines Agency (EmA) issued a draft of revised guideline on the environmental risk assessment of medicinal products for human use. The revised guideline upgrades the first guidelines published in 2006 and provide a more consistent and comprehensive approach to environmental risk assessment. Thus, in terms of greater transparency, a decision tree approach was introduced that clearly illustrates substances properties that trigger the need for its testing and evaluation. At the same time, the guideline defines the risk assessment approach for each environmental compartment more clearly. The revision of a twotiered assessment approach also reduces administrative burden, since the revised guideline provides more detailed technical guidance to applicants and allows the introduction of risk reduction measures in the second phase. The draft guideline also defines the tailored risk assessment approach for potential endocrine active substances and antibiotics. The updated guideline thus provides an improved guidance for environmental risk assessment and introduces more precisely evaluation of the influence of the active substances on development and reproduction as well as on the endocrine system.
Keywords: bioakumulativnost; obstojnost; ocena tveganja za okolje (ERA); Okolje; predvidena koncentracija v okolju (PEC); strupenost; Zdravila